Organizational Citizenship Behavior Sebagai Mediator Antara Motivasi dan Kepemimpinan Transformasional terhadap Kinerja Pegawai - Gede Iwan Santika; Anak Agung Dwi Widnyani; Anak Agung Made Sastrawan Putra (Universitas Batanghari, 2023)
Improving performance is very important for an organization to face a rapidly changing environment. Performance is an organizational barometer to determine the achievements that have been realized. Statistics Indonesia performance achievement is the achievement of the indicators of strategic objectives in the current year. There are four strategic goals that become BPS performance targets. Three of the four strategic goals have not been able to be realized by Statistics Indonesia throughout the Province of Bali. This condition is reflected in the average achievement value which has not reached 100 percent. Based on some of the results of previous studies, this research analyzes how motivation and transformational leadership have a direct effect on employee performance and an indirect effect on employee performance through Organizational Citizenship Behavior (OCB) mediation. The results obtained from data analysis using CB-SEM through Lisrel 10.2 software are motivation influencing OCB but not influencing employee performance, transformational leadership influencing OCB and employee performance, OCB influencing employee performance, OCB mediating the effect of motivation on employee performance, and OCB mediates the effect of transformational leadership on employee performance.